Detoxification of Jatropha curcas seed cake in solid-state fermentation of newly isolated endophytic strain and nutrition assessment for its potential utilizations. (April 2016) - Zhang, Xiaoyu; Yang, Zehong; Liang, Jian; Tang, Lin; Chen, Fang
Abstract: In this study, the zxy-12 strain was newly isolated from the seed kernel of Jatropha curcas. Jatropha seed cake (JSC) was one by-product generated after the biodiesel industry. The solid-state fermentation (SSF) of the zxy-12 strain was exploited for the detoxification of JSC as a growth substrate. The zxy-12 strain showed a high degradation efficiency of phorbol esters (PEs) or derivatives and curcin. The SSF parameters were optimized for the maximum degradation of PEs or derivatives. The quantitative analysis of PEs or derivatives was established by the high performance liquid chromatography (HPLC) method. PEs or derivatives in JSC were well separated to seven individual peaks, that was similar to the HPLC chart of Jatropha curcas fractions (JCF). Under the optimized conditions, the maximum removal of PEs or derivatives was obtained at the ratio of 92.78% (w w −1 ) as the main toxicant in JSC. In fermented JSC, the crude fat was significantly reduced by 5.53%. Crude proteins and small peptides were greatly increased by 15.11% and 19.61%, respectively, and exceeded soybean meal by 6.2% and 9.93%, respectively. The amino acid composition also significantly increased. Our results suggested that SSF by the zxy-12 strain was a viable detoxification approach to utilize the huge amount of JSC. Highlights: The zxy-12 strain was isolated, characterized and could efficiently biodegrade PEs or derivatives and curcin in JSC. The solid-state fermentation parameters was analyzed and optimized. HPLC method was established for the quantitative analysis of PEs or derivatives in JSC. The nutritional compositions were determined. JSC is a good-quality protein source for potential utilization in animal feeding and food applications.